Features of use of modular training system armsportsmens 16–17 year olds in the annual macrocycle - Безкоровайний Дмитро Олександрович (Dmytro Bezkorovainyi); Камаєв Олег Іванович (Oleg Kamaev) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to determine the most effective ratio of different means and methods of training 16–17 year olds armsportsmens the application of the block training system in the annual macrocycle. Material and Methods: 30 armsportsmens investigated 16–17 years to 15 in the control and experimental groups, analyzed and summarized the data of scientific and methodical literature, conducted teacher testing, pedagogical experiment, methods of research used functional state of cardio-respiratory. Results: it was found that the block system of training 16–17 year olds armsportsmens allows significantly increase the level of morphological and functional training base, improves functional indices of the cardiovascular system. Conclusions: the experimental training program for 16–17 year olds armsportsmens based modular training system allowed the athletes to create the experimental group was significantly higher level of morphofunctional sports training base, significantly improve the functionality of the body athletes, contributed to a high level of fitness and sports is recommended to practice the preparation armsportsmens.